Implementasi Sidang Keliling di Pengadilan Agama Garut menurut Maslahah Mursalah - Salma Siti Safira; Shindu Irwansyah (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. The mobile court is one of the services provided by the Religious Courts to help facilitate justice seekers who are constrained by geographical, transportation, social and economic conditions to come to the court office. Maslahah mursalah is one of the theories of extracting law in Islam when there are no rules in the Qur'an or hadist. Researchers in their research formulate the formulation of the problem as follows: How are the provisions of maslahah in determining Islamic law; How is the concept and implementation of the circuit court at the Garut Religious Court; What is the impact of the implementation of the circuit court at the Garut Religious Court according to maslahah mursalah; The purpose of this research is to answer the formulation of the problem. This research is a field research, using qualitative descriptive analysis techniques. The results of his research that the circuit court at the Garut Religious Court is in accordance with the maslahah mursalah theory because it contains benefits that are in line with the goals of Islamic law but are not regulated by sharia; the concept and implementation of the circuit court at the Garut Religious Court in accordance with the provisions of the applicable procedural law. And the circuit court at the Garut Religious Court seen from the level of benefit is a hajjiyah maslahah. Abstrak. Sidang keliling adalah salah satu bentuk pelayanan yang diberikan Pengadilan Agama untuk membantu memudahkan para pencari keadilan yang terkendala oleh kondisi geografis, transportasi, sosial maupun ekonomi untuk datang ke kantor pengadilan. Maslahah mursalah merupakan salah satu teori penggalian hukum dalam Islam ketika tidak ada aturan dalam Al-Qur’an maupun hadist. Peneliti dalam penelitiannya merumuskan rumusan masalah sebagai berikut: Bagaimana ketentuan maslahah dalam penentuan hukum Islam; Bagaimana konsep dan implementasi sidang keliling di Pengadilan Agama Garut; Bagaimana dampak implementasi sidang keliling di Pengadian Agama Garut menurut maslahah mursalah; adapun tujuan dari penelitian ini yaitu menjawab rumusan masalah. Penelitian ini merupakan penelitian lapangan (field research), menggunakan teknik analisis deskriptif kualitatif. Hasil penelitiannya bahwa sidang keliling di Pengadilan Agama Garut sesuai dengan teori maslahah mursalah karena mengandung kemaslahatan yang sejalan dengan tujuan syariat Islam tetapi tidak diatur oleh syara; konsep dan implementasi sidang keliling di Pengadilan Agama Garut sesuai dengan ketentuan hukum acara yang berlaku. Dan sidang keliling di Pengadilan Agama Garut dilihat dari tingkat kemaslahatannya merupakan maslahah hajjiyah.